The mediating role of frequent mental distress in the relationship between adverse childhood experiences and cognitive disability in emerging adults - Yanyan Sun; Shifang Qu; Zhiyao Li; Weixin Zhang; Yiwen Meng; Jiaxin Fang; Shunyao Shi; Siyu Zhu; Nana Liu; Huifang Song; Kun Tang; Xinyao Zhang; et al. (Scientific Reports)
Abstract Adverse Childhood Experiences (ACEs) may have an impact on cognitive disability through multiple pathways. Frequent Mental Distress (FMD) could result in cognitive disability through different aspects, but the potential mediating role of FMD in the associations remained unclear. So we aimed to investigate not only the association between self-reported ACEs and cognitive disability, but also the mediating effect of FMD between ACEs and cognitive disability. A cross-sectional analysis of respondents aged 18–25 years old in the 2020 and 2021 Behavioral Risk Factor Surveillance System (BRFSS) was performed. Weighted multivariate logistic regression models were used to assess the association of ACEs with FMD and cognitive disability. Mediation effects were used to investigate FMD as mediation between ACEs and cognitive disability in emerging adults. Among the 10,309 respondents, the prevalence of cognitive disability was 15.8%, and 71.6% of them experienced ACEs. We found experienced ACEs, self-reported FMD were significantly associated with 4.05 and 5.61 times increased risk of cognitive disability, respectively. The more types of ACEs respondents experienced, the higher risks of cognitive disability. And mediating effect analysis found FMD mediated the associations between ACEs and cognitive disability. Our study indicated a strong association between ACEs and cognitive disability in emerging adults. Furthermore, FMD plays a mediating role in the associations.